Broad Money Demand and Monetary Policy in Tunisia - Treichel, Volker (IMF Working Papers; Working Paper ;, 1997)
The development of empirical foundations to the conduct of monetary policy in Tunisia is the central concern of this paper. Finding stable money demand functions, it broadly corroborates the choice of monetary aggregates as intermediate targets of monetary policy by the Tunisian Central Bank. It finds, however, a lower income elasticity than the one currently applied by the Central Bank and proposes a different methodology for defining monetary growth targets. The paper also finds that both interest rates and reserve money are feasible operating targets and suggests that the Central Bank orients its monetary policy more towards transparent operating targets.